A benzimidazole-based fluorescent chemosensor for Cu2+ recognition and its complex for sensing H2PO4− by a Cu2+ displacement approach in aqueous media. Issue 39 (28th September 2016) - Goh, Hanna; Ko, Yoon Gun; Nam, Tae Kyu; Singh, Amanpreet; Singh, Narinder; Jang, Doo Ok
Graphical abstract: Highlights: Benzimidazole-based receptor3 recognizes Cu 2+ selectively in aqueous medium. Complex3 –Cu 2+ exhibits selective sensor properties for sensing H2 PO4 − . The LOD of receptor3 for sensing Cu 2+ is low enough for real samples. Abstract: A benzimidazole-based dipodal receptor was designed and synthesized. The receptor recognized Cu 2+ ions selectively in an aqueous medium in the presence of other metal ions. The resultant complex displayed selective sensing ability toward H2 PO4 − via a metal displacement process. The detection limits of the receptor to Cu 2+, and the resultant complex to H2 PO4 −, were calculated to be 9.76 and 1.41 μM, respectively. These values are sufficiently low indicating that this system shows good potential for application in biological and environmental sample analyses.